Layanan Bimbingan dan Konseling bagi Anak Perantau di Sekolah Dasar Negeri di Purbalingga - Ambar Wijayaningsih; Novan Ardy Wiyani; Tri Damayanti (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2022)
This study aimed to describe the model of guidance and counselling services provided by teachers to students at State Elementary School 1 Tunjungmuli Purbalingga. This research uses a qualitative approach with the type of case study research. The subjects in this study included school principals, class teachers who served as guidance and counselling teachers, children of immigrants, and guardians of students. Data collection techniques use interviews, observation, and documentation. The data was analyzed by reducing, presenting, and drawing conclusions. The results showed that guidance and counselling services for overseas students were carried out through four types of guidance, namely personal, social, study, and career guidance. Guidance and counselling services in class VI have not achieved maximum results, but guidance and counselling services in class II are optimal. Guidance and counselling services are provided by personal, social, study, and career guidance services. The result of the research is that counselling services for children of nomads are more effective when using tutoring services. Problems with learning are the biggest problems faced by immigrant children.